Design and development of an automatic device for milling and separating multi-size rice husk grains - Farah Raihan Zainuddin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
There are many ways to exploit rice husk include using it for manufacturing process for honeycomb structure. The project is to be part of the study to design and create more productrive ways in core honeycomb structure made of rice husk grain and polymer mixture. The size needed for the honeycomb to get a good structure is by having the rick husk grains in small partical so the structure will be strong. For this project, the object is to get a new design of blade that are suitable for blending the multi-size husk grains.